High Power Factor DCM-CRM Cuk PFC Converter with Wide Input Voltage Range Utilizing Variable Inductor Control - Tiesheng Yan; Ruihao Liu; Hao Wen; Guohua Zhou (Applied Sciences)
The Cuk power factor correction (PFC) converter with an input inductor operating discontinuous conduction mode (DCM) is widely utilized for its advantages of continuous input and output currents, low output voltage ripple, and simple control. However, the conventional Cuk PFC converter encounters issues such as the inability to achieve high power factor (PF) because of input current distortion and high intermediate capacitor voltage, especially at high input voltage. To achieve high PF, high efficiency, and low intermediate capacitor voltage simultaneously, by operating the output inductor at critical conduction mode (CRM) and adjusting input inductance from 170 µH to 930 µH within the half-line cycle dynamically with the transient rectified input voltage, a DCM-CRM Cuk PFC converter utilizing variable inductor control is proposed in this paper. The topology operational principle, control strategy, and key characteristics of the proposed converter have been studied. A 108 W experimental prototype was built and tested to validate the proposed converter. According to the comparative experimental results between the conventional converter and the proposed converter, it can be concluded that the proposed converter utilizing variable inductor control can enhance the PF and efficiency and reduce the intermediate capacitor voltage and total harmonic distortion (THD) of input current with universal 90~240 Vac input voltage range.